Food supplement consumption does not related to self-reported symptoms of covid-19 among students in Binawan University - Mia Srimiati; Adhila Fayasari; Angga Rizqiawan; Lina Agestika (AcTion: Aceh Nutrition Journal, 2020)
The world is facing a pandemic of COVID-19. Multivitamin and other supplement is already known can improve immunity and prevent infected by the virus. The purpose of this study was to determine the relationship of multivitamin/supplement intake with the appearance of COVID-19 symptoms. The method of this study was analytic surveys with cross-sectional designs. The questionnaire was distributed twice, the first distribution phase involved 423 respondents to determine the consumption habits of supplements and the appearance of COVID-19 symptoms. Then, from the respondents who consumed supplements, the second questionnaire was sent again, to find out the type of supplements consumed, and only 127 respondents returned completely. As a respondent, we involved students of Binawan University, Jakarta, Indonesia. We used Pearson Chi-Square and Fischer exact test for statistical analysis. The results of this study noted that 67.7% of respondents consumed supplements/multivitamin, 94.8% of respondents did not show symptoms of COVID-19. The type of supplement consumed by most respondents was vitamin C (51.2%), while multivitamins / other vitamins were 20.1%. In conclusion, based on statistical analysis, there was no significant relationship between supplement consumption with the appearance of COVID-19 and conditions in carrying out daily activities on respondents who show COVID-19 symptoms